PENGARUH VARIASI SELIMUT BETON TERHADAP KUAT LENTUR BALOK BERTULANG BAJA RINGAN PROFIL C - Indrawan, Akbar; Bagaskara, M Kevin; Suhadi, Suhadi; Subrianto, Agus (PILAR, 2025)
Concrete is one of the most widely used construction materials due to its ease of production and relatively low cost. However, it has several drawbacks, such as brittleness and low tensile strength. This study aims to investigate the effect of concrete cover thickness on the flexural strength of reinforced concrete beams using cold-formed steel C-profile reinforcement. The specimens were concrete beams measuring 150 × 150 × 700 mm with six variations: a control beam (B0) and beams with cover thicknesses of 8.6 mm (B1), 30 mm (B2), 45 mm (B3), 60 mm (B4), and 75 mm (B5). After 28 days of curing, the specimens were tested for compressive strength and flexural strength. The results indicate that increasing the cover thickness leads to a reduction in flexural strength. The highest average flexural strength was obtained at 8.6 mm cover thickness (13.1 MPa), while the lowest was observed at 75 mm cover thickness (5.9 MPa). Therefore, the use of cold-formed steel C-profile reinforcement can improve beam performance, but the cover thickness must be carefully considered to achieve optimal flexural strength